2013
DOI: 10.1007/s13317-013-0048-5
|View full text |Cite
|
Sign up to set email alerts
|

Intravenous immunoglobulin therapy in vasculitic ulcers: a case of polyarteritis nodosa

Abstract: IntroductionPolyarteritis nodosa (PAN) is a systemic necrotizing medium-size-vessel vasculitis with variable clinical manifestations. Diagnosis is confirmed by histology or angiography. The mainstay of treatment is corticosteroids alone or combined with cyclophosphamide (CYF).Case reportSeventy-one-year-old female, follow-up started in 1997 at the age of 56 for suspected relapsing febrile viral exanthema. Skin biopsy was performed and the diagnosis of lymphomatoid papulosis was made, with complete response to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
(25 reference statements)
0
5
0
Order By: Relevance
“…GC with concomitant use of CY or MTX is recommended as a standard treatment for PAN ( 2 ), and various immunosuppressive treatments, including RTX, have been used for refractory cases ( 3 - 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…GC with concomitant use of CY or MTX is recommended as a standard treatment for PAN ( 2 ), and various immunosuppressive treatments, including RTX, have been used for refractory cases ( 3 - 5 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the basis of data from numerous reports, 40-45% of patients develop a lower-limb neuropathy, more commonly a multifocal neuropathy than a distal polyneuropathy 78,[80][81][82][83][84][85] . Reports of nerve biopsies in patients with cutaneous polyarteritis nodosa are rare, but one revealed vasculitis 86 . The incidence of myopathy has not been adequately investigated, but in one study, all five muscle biopsy samples demonstrated necrotizing vasculitis 77 .…”
Section: Diabetic Lumbosacral Radiculoplexus Neuropathymentioning
confidence: 99%
“…[20] In patients with resistant or relapsed disease, the role of intravenous immunoglobulin as a successful option for the treatment of skin lesions has been highlighted in 2 case reports. [21,22] Moreover, the effectiveness of vasodilators and antithrombotic agents, such as prostaglandin I2 analogues, has been reported, especially in the treatment of the skin ulcers and gangrene associated with cPAN [23] and other types of vasculitis. [24] Less aggressive treatments may be warranted in cPAN, as it is not usually associated with life-threatening or progressive outcomes.…”
Section: Discussionmentioning
confidence: 99%